2001
DOI: 10.1046/j.1440-1827.2001.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of N‐cadherin and α‐fetoprotein in stomach cancer

Abstract: Although N-cadherin is necessary for organ formation originating in the endoderm, the expression of N-cadherin in gastric carcinoma and its role has not yet been reported. The present study was conducted to determine the pattern of immunohistochemical expression of E-cadherin and N-cadherin, using formalin-fixed, paraffin-embedded tissues from 97 primary gastric carcinomas, including 17 which were producing alpha-fetoprotein (AFP). Samples were subdivided into 50 tubular adenocarcinomas and 47 poorly different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Interestingly, it has been previously reported that N-cadherin is expressed by a-foetoprotein-positive gastric hepatoid adenocarcinomas. 31 Another diagnostic issue is to discriminate primary intrahepatic cholangiocarcinomas from hepatocellular carcinomas. As the hepatocytes also express N-cadherin at their plasma membrane, this marker cannot 'per se' distinguish hepatocellular carcinomas from intrahepatic cholangiocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been previously reported that N-cadherin is expressed by a-foetoprotein-positive gastric hepatoid adenocarcinomas. 31 Another diagnostic issue is to discriminate primary intrahepatic cholangiocarcinomas from hepatocellular carcinomas. As the hepatocytes also express N-cadherin at their plasma membrane, this marker cannot 'per se' distinguish hepatocellular carcinomas from intrahepatic cholangiocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancers, de novo expression of mesenchymal cadherins, N‐cadherin, and cadherin‐11, is observed in the poorly differentiated areas where E‐cadherin expression is lost or aberrant, suggesting that a ‘cadherin switch’ from epithelial to mesenchymal cadherins is related to the transition from a benign to invasive phenotype 18 . However, N‐cadherin is detected in AFP‐producing gastric adenocarcinomas with normal E‐cadherin expression, 19 and directly promotes cell motility and invasion in breast cancer cells 11 . Several molecular mechanisms have been proposed, which include N‐cadherin‐mediated dynamic adhesion between tumor cells, interactions with the surrounding stromal cells, 18,20 activation of fibroblast growth factor receptor, 11 and prevention of cell apoptosis by inhibiting the increase in intracellular free calcium 21 .…”
Section: Discussionmentioning
confidence: 99%
“…N-cadherin was found back in metastasising melanomas (Matsuyoshi et al, 1997;Sanders et al, 1999). In gastric carcinoma N-cadherin was found in all α-foetoprotein producing tumours (Yanagimoto et al, 2001) and a correlation was found between the expression of twist and N-cadherin expression (Rosivatz et al, 2002). During early development N-cadherin is found in some basal granulated epithelial cells of the stomach, duodenum and jejunum (Gaidar et al, 1998).…”
Section: N-cadherin and Cancermentioning
confidence: 99%